Strategies and Teaching Approaches for Enhancing Mathematical Foundation of New Students in Vocational Certificate Program, Pre-Engineering Curriculum - Phatchat, Sompop; Kitidet, Hussapong; Kooha, Metapiya; Ode-sri , Adisorn; Leelasopawut, Rungkan (Journal of Technical and Engineering Education, 2025)
Abstract This research aimed to develop strategies and teaching approaches for enhancing mathematical foundation of first-year students in Vocational Certificate Program, Pre-Engineering Course, Academic Year 2024. In addition to literature reviews, qualitative methods were employed including: 1) in-depth interviews with 3 students and 3 instructors, and 2) focus group interviews with one group of faculty members (3 participants) and one group of students (4 participants) to gather data, identify problems, and collect recommendations before conducting diagnostic analysis to filter and establish 7 awareness-based strategies. These strategies serve as prototype guidelines for stakeholders to use as operational principles, subsequently connecting to the determination of teaching approaches comprising existing approaches, ad-hoc approaches, and newly designed approaches, totaling 4 approaches. Approach 2 was selected: 4 days per week, 18:00 - 20:00, for 3 consecutive weeks, as it relates to all strategies, is convenient for all parties, and provides the most comprehensive problem-solving capability. In practice, the sample consisted of 60 students who scored below 50% on the basic mathematics knowledge assessment “Pre-test,” with an average score of 8.48. After completing the foundation enhancement process and taking the “Post-test” assessment, the sample group achieved an average score of 12.75 out of 30 total points, showing a statistically significant difference at the .05 level (t = 12.859, p < 0.001). The satisfaction evaluation results regarding the foundation learning were at a “high” level, with instructor personality and competence receiving the “highest” satisfaction level, followed by application and teaching approaches. The area that “needs improvement” was time scheduling, as students felt tired from regular classes. The research findings can be used as a model or guideline to enhance effectiveness and determine directions for mathematical foundation enhancement for first-year students in various curricula.